Development of the premixing injector in burner system - Sies, Mohamad Farid (2013)
The alternative fuel is good attention especially for renewable and prevention energy such as biodiesel. Biodiesel fuel (BDF) has a potential for external combustion. BDF is one of the hydrocarbon fuels. Palm oil Biodiesel is free from sulfur and produced by esterification and transesterification reaction of vegetable oil with low molecular weight alcohol, such as ethanol or methanol. The objectives of this research are design the mixing injector fuel and water-fuel emulsion with air for open burner and analyze the behavior of mixture spray formation between fuel (DF and BDF) and water-fuel emulsion. Premix injector use for external combustion especially open burner system. The disadvantages of BDF are high toxic emissions such as NOx, CO and particular matter (PM) and but it can reduced the performance of burner system. High toxic emission can be solved by using a new concept injector with mixing fuel-water emulsion and air. The additional water for combustion process can reduce the NOx emissions, soot, and the flame temperature. This research focuses the Spray angle, penetration, and flame length with secondary and without secondary air. CPO biodiesel has longer penetration length and spray area than diesel, but the spray angle is smaller than diesel. The different of flame Image between pure fuel and water mix with fuel is the flame color. Water mix with fuel has brightness color and shorter flame than pure fuel.